Pengaruh Modal dan Investasi Teknologi terhadap Pertumbuhan Ekonomi Provinsi Nangroe Aceh Darusalam Setelah Dibelakukan Syariat Islam - Safriadi M Yunus Aks (Universitas 45 Surabaya, 2024)
The existence of the policy of the Government of the Republic of Indonesia, providing special autonomy to the Province of Nangroe Aceh Darussalam (NAD) through the concept of asymmetric decentralization, accompanied by the issuance of a law implementing Islamic Sharia in Aceh in a comprehensive manner, as well as opening up opportunities for the government and the people of Aceh Province to increase the rate of economic development which is based on religious values. The aim of this research is to analyze the influence of capital issued by the government and technology investment on the regional economic growth of Aceh province. The target population is districts/cities in Aceh Province, while the sample consists of 23 analysis units (5 cities and 18 districts). Secondary data is on a ratio scale, to measure research variables, namely; capital, technology investment and regional economic growth for the 2011 - 2020 period, sourced from the NAD Provincial Central Statistics Agency. Data analysis techniques use descriptive statistics and regression analysis to test research hypotheses. The research results show that, specifically and simultaneously, capital and technology investment have a significant influence on the regional economic growth of Aceh Province. Partially, capital and technology investment are determinants of regional economic growth in Aceh Province. These two variables have the effect of increasing regional economic growth. Provinces that have large capital and investment in quality and innovative technology will have an impact on high economic growth in Aceh Province. Thus, it indicates that in general the intensity of implementation of Islamic Sharia in Aceh province has provided a meaningful role for the capital sector and technology investment in increasing regional economic growth.